Supply Chain Relationships in Omnichannel Retailing - Dimitrova, Violeta (Research Papers, 2023)
The omnichannel supply chain changes the relationship between vertical and horizontal market agents. The author advocates the thesis that the cooperation between the participants in the supply chain and the cross-functional integration inside the company are key factors for the success of the commercial business in the conditions of digitalization. The aim of the study is to analyze the impact of retail transformations on supply chain relationships in an omnichannel environment. The object of research is the transformation of business models in retail trade through integration and convergence of marketing and logistics operations, symbiosis between online and offline sales and creation of omnichannel models.
Keywords: Business model; Marketplace; Retailing; Supply chains; Omnichannel